Analisis Promosi pada Aplikasi Layanan Pesan Antar Makanan terhadap Perilaku Konsumen - Silmi Asy-Syifaa; Maula Diah Liani; Melvin Christian Abimanyu; Elsya Rahmalia Hidayat; Hana Alifah Putri; Nabila Yusuf; Rama Wijaya Abdul Rozak (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study aims to analyze the impact of promotions on food delivery service applications on consumer behavior. The focus of the research is on the use of the GoFood feature in the Gojek application. The method used is descriptive quantitative, by collecting data through a questionnaire (questionnaire) given to 115 GoFood service users. This questionnaire includes questions about how consumer behavior patterns are related to the promotions provided. The results of this study are that most consumers feel benefited and promotions direct their behavior in a positive direction. A small proportion of consumers feel that promotions direct their behavior in a negative direction. As for certain users, the use of promotional features does not really affect the emergence of positive or negative behavior patterns.